(untitled) (Veterinary Science, 2024)
This work aims to offer information about the diagnosis and the medical management of toxoplasma gondii infection in a ring-tailed lemur mix squad composed of 5 individuals (3 males and 2 females) under human care in a zoo collection of the 6th region of Chile. The 8-year-old female was presented with fever, lethargy, appetite loss, and abortion of a newborn at term. A clinical exam was performed, and hematologic and biochemistry tests, in addition to serology of infectious diseases under anesthesia to the mother and histopathology on the hatchling. The results show Toxoplasma gondii central nervous infection on the hatchling with no other scientific evidence. Cited in the literature, there is some evidence that lemurs are one of the most susceptible species to toxoplasma infection, and sometimes the diagnosis is challenging, after 6 years with no newborns, and after 4 months of treatment, a healthy hatchling was born.